EURO-MUSCULUS/USPRM Dynamic Ultrasound Protocols for Knee - Pirri, Carmelo; Stecco, Carla; Güvener, Orhan; Mezian, Kamal; Ricci, Vincenzo; Jačisko, Jacuk; Novotný, Tomáš; Kara, Murat; Chang, Ke-Vin; Dughbaj, Muhammad; Jain, Nitin B; Özçakar, Levent (American journal of physical medicine & rehabilitation, 2023)
In this dynamic scanning protocol, ultrasound examination of the knee is described using various maneuvers to assess different conditions. Real-time patient examination and scanning videos are used for better simulation of the daily clinical practice. The protocol is prepared by several/international experts in the field of musculoskeletal ultrasound and within the umbrella of European Musculoskeletal Ultrasound Study Group in Physical and Rehabilitation Medicine/Ultrasound Study Group of the International Society of Physical and Rehabilitation Medicine.
Keywords: koleno; Knee; Ultrasonography; Knee Joint; ultrasonografie; rehabilitační lékařství; muskuloskeletální nemoci; kolenní kloub; Humans; Muscles; svaly; Musculoskeletal Diseases; lidé; Physical and Rehabilitation Medicine